IoT-based smart aeroponics vertical farming system for optimized plant growth - Ho, Yih Hwa; Lee, Zhao Lun; Chia, Sia Liang; Thong, Chan Foong; Rosdi, Farah Natasha; Ramlee, Nur Ezzatul Shahira (Research and Scientific Innovation Society, 2025)
This paper presents the design and development of an IoT-based smart aeroponics vertical farming system intended to improve plant growth efficiency through continuous microclimate monitoring, automation, and optimized water–nutrient delivery. The system integrates Arduino Uno as the main controller with sensors including a light-dependent resistor (LDR), DHT11 temperature–humidity sensor, ultrasonic water-level sensor, and electromechanical actuators such as a water pump and solenoid valve. IoT connectivity is enabled through the ESP8266 Wi-Fi module, interfacing with the Blynk platform for real-time monitoring, data logging, and remote operation. The vertical tower design incorporates a multi-layered aeroponic structure allowing 7 plants per column while minimizing land usage, water consumption, and human intervention. Hardware development includes fabrication of the aeroponic tower, nutrient delivery system, and automated water-refill mechanism. Experimental results demonstrate effective luminance-based irrigation control, humidity–temperature notifications, autonomous water-level regulation, and successful plant growth over a 7-day trial using green beans. The system achieved reliable environmental sensing, responsive actuation, and stable communication with the IoT server. The findings highlight the potential of low-cost IoT-enabled aeroponics as a sustainable agricultural approach for urban environments. Recommendations for system enhancement and scalability are also discussed.